Utilitarian, hedonic, and self-esteem motives in online shopping - Indrawati, I. (Emerald Group Holdings Ltd., 2022)
Purpose: The study aims to analyze the influence of hedonic, utilitarian, and self-esteem motivations on online shopping behavior. Likewise, the mediating role of impulsive shopping and shopping intentions is also analyzed. Design/methodology/approach: The study was carried out with the results of a survey in which 450 respondents participated, and the data was analyzed by using structural equation modeling (SmartPLS 3.0 software). Findings: All the hypothesized links were significant and positive except for the relationship of self-esteem motive with impulsive shopping tendency, which was negative as hypothesized. Moreover, hedonic motive had a strong positive impact on impulsive shopping tendency, whereas, in contrast, utilitarian motive had a strong positive impact on shopping intentions. Practical implications: Managers should focus on functional value rather than emotional value to attract customers who tend to be utilitarian. In contrast, for customers who tend to be hedonic, the product offerings should be visually appealing, stimulating and inspiring, as well as have emotional value. Originality/value: This study investigates the roles of self-esteem and hedonic motives in impulsive shopping behavior. Moreover, by using the theory of planned behavior, this study highlights the roles of hedonic and utilitarian motives in attitude toward engaging in online shopping. Â© 2022, Indrawati Indrawati, Gadang Ramantoko, Tri Widarmanti, Izzatdin B.A. Aziz and Farhat Ullah Khan.